Corrosion behavior of 20# steel in aqueous CO2 solution under stratified gas-liquid two-phase flow condition. Issue 1 (7th January 2019) - Yang, Guirong; Song, Wenming; Wang, Fuqiang; Ma, Ying; Hao, Yuan
Abstract : Purpose: This paper aims to investigate the corrosion rate, surface morphology and composition of corrosion products of 20# seamless steel in aqueous CO2 solution under stratified gas-liquid two-phase flow condition. The development of a corrosion products layer has also been discussed. Design/methodology/approach: The following methods were used: weight loss method, scanning electron microscopy, energy-dispersive X-ray spectroscopy and X-ray diffraction. Findings: The corrosion rate curve presents an irregular zigzag change trend with a gradual increase in time. The peak value of the corrosion rate appears when the corrosion time is 4 h and 8 h. The corrosion products layer is composed of two sub-layers: the inner dense layer that is about 6 µm thick and the outer loose layer that is about 9 µm thick when the corrosion time is 8 h. The main corrosion product are FeCO3 and Fe2 O3 . Originality/value: The atomic ratio of Fe/C/O is relatively stable for the inner dense layer, but changes in thickness for the outer loose layer. There is a densification stage after a loose corrosion products layer forms, and it is periodic.